1992
DOI: 10.1056/nejm199212243272604
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Trimethoprim–Sulfamethoxazole or Aerosolized Pentamidine for Secondary Prophylaxis of Pneumocystis carinii Pneumonia in Patients with the Acquired Immunodeficiency Syndrome

Abstract: In patients with AIDS who are receiving zidovudine, trimethoprim-sulfamethoxazole is more effective than aerosolized pentamidine in conventional doses for the prevention of recurrent pneumocystis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
156
1
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(163 citation statements)
references
References 13 publications
4
156
1
2
Order By: Relevance
“…TMP-SMZ is the most effective drug for PCP prophylaxis [2,[8][9][10]. TMP inhibits dihydrofolate reductase and SMZ inhibits dihydropteroate synthetase.…”
Section: Discussionmentioning
confidence: 99%
“…TMP-SMZ is the most effective drug for PCP prophylaxis [2,[8][9][10]. TMP inhibits dihydrofolate reductase and SMZ inhibits dihydropteroate synthetase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, new data suggested that dapsone/ pyrimethamine [ 10] and possibly trimethoprim-sulfamethoxazole [24] prevent toxoplasmosis. Meanwhile, administration of trimethoprim-sulfamethoxazole became the standard prophylaxis for PCP [5,6,25], and continuing the prophylactic administration of aerosolized pentamidine to patients who were seropositive for toxoplasmosis seemed unethical. The trial was therefore stopped prematurely as of 31 December 1992.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis with trimethoprim-sulfamethoxazole also appears to protect against toxoplasmic encephalitis, but the optimal dose is unknown and the assessments of efficacy have been based only on a retrospective analysis [24], observational data [34,35], or results of controlled trials that did not primarily target prophylaxis for toxoplasmic encephalitis and therefore yielded small numbers of events [5,6,31,[36][37][38]. While none of these trials revealed a significant protective effect on an intent-to-treat basis, toxoplasmic encephalitis in fact rarely occurred during treatment with trimethoprim-sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations